Impact of asylum on receiving countries - Susan F. Martin; Andrew I. Schoenholtz; David Fisher (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Whereas asylum seekers and the systems for adjudicating their claims to refugee status in developed countries have garnished considerable attention and, often, have been at the centre of political controversy, there has been relatively little research on their actual impact on receiving countries. This article discusses the factors that determine the impact of asylum, as distinct from other forms of migration, concluding that the number of asylum seekers, government policies and socioeconomic characteristics all determine the impact of asylum. Hence, the impacts of asylum can differ significantly from country to country. Even within the same country, one could expect to see varied impacts depending on the age, education and skill level of individual asylum seekers. The paper then examines the fiscal, economic, and social impacts of asylum, as well as its impact on foreign policy and national security. It concludes with an examination of the impact of developed countries' asylum policies on the protection of refugees in developing countries. When refugee protection has been weakened in economically strong states and asylum restrictions are perceived as burden shifting, international protection in the developing world where most refugees try to survive has been undercut.
Keywords: F22; H50; 330; asylum; fiscal impact; economic impact; national security